Differences in Reach and Attrition Between Web-Based and Print-Delivered Tailored Interventions Among Adults over 50 Years of Age: Clustered Randomized Trial - Peels, Denise Astrid; Bolman, Catherine; Golsteijn, Rianne Henrica Johanna; De Vries, Hein; Mudde, Aart Nicolaas; van Stralen, Maartje Marieke; Lechner, Lilian (JMIR Publications, 2012)
BackgroundThe Internet has the potential to provide large populations with individual health promotion advice at a relatively low cost. Despite the high rates of Internet access, actual reach by Web-based interventions is often disappointingly low, and differences in use between demographic subgroups are present. Furthermore, Web-based interventions often have to deal with high rates of attrition. ObjectiveThis study aims to assess user characteristics related to participation and attrition when comparing Web-based and print-delivered tailored interventions containing similar content and thereby to provide recommendations in choosing the appropriate delivery mode for a particular target audience. MethodsWe studied the distribution of a Web-based and a print-delivered version of the Active Plus intervention in a clustered randomized controlled trial (RCT). Participants were recruited via direct mailing within the participating Municipal Health Council regions and randomized to the printed or Web-based intervention by their region. Based on the answers given in a prior assessment, participants received tailored advice on 3 occasions: (1) within 2 weeks after the baseline, (2) 2 months after the baseline, and (3) within 4 months after the baseline (based on a second assessment at 3 months). The baseline (printed or Web-based) results were analyzed using ANOVA and chi-square tests to establish the differences in user characteristics between both intervention groups. We used logistic regression analyses to study the interaction between the user characteristics and the delivery mode in the prediction of dropout rate within the intervention period. ResultsThe printed intervention resulted in a higher participation rate (19%) than the Web-based intervention (12%). Participants of the Web-based intervention were significantly younger (P<.001), more often men (P=.01), had a higher body mass index (BMI) (P=.001) and a lower intention to be physically active (P=.03) than participants of the printed intervention. The dropout rate was significantly higher in the Web-based intervention group (53%) compared to the print-delivered intervention (39%, P<.001). A low intention to be physically active was a strong predictor for dropout within both delivery modes (P<.001). The difference in dropout rate between the Web-based and the printed intervention was not explained by user characteristics. ConclusionsThe reach of the same tailored physical activity (PA) intervention in a printed or Web-based delivery mode differed between sociodemographic subgroups of participants over 50 years of age. Although the reach of the Web-based intervention is lower, Web-based interventions can be a good channel to reach high-risk populations (lower PA intention and higher BMI). While the dropout rate was significantly higher in the Web-based intervention group, no specific user characteristics explained the difference in dropout rates between the delivery modes. More research is needed to determine what caused the high rate of dropout in the Web-based intervention. Trial RegistrationDutch Trial Register (NTR): 2297: http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=2297 (Archived by WebCite at http://www.webcitation.org/65TkwoESp).